Teaching Note—Social Work Serial: Using Video-Recorded Simulated Client Sessions to Teach Social Work Practice. (3rd April 2018) - Asakura, Kenta; Bogo, Marion; Good, Bethany; Power, Roxanne
ABSTRACT: Simulation, the use of trained actors as simulated clients, has gained empirical support as an effective teaching and assessment method in social work education. The associated costs involving the use of live simulation, however, often pose a barrier and prevent less resourced schools from implementing this pedagogical approach in the classroom. Social Work Serial is a pedagogical project that used video-recorded simulated client sessions as an alternative to live simulation. In this teaching note, we will describe step-by-step production and implementation processes involving the project and discuss the implications of video-based simulation for social work education.